Towards a Circular Economy: Government Policy in Waste Management Based on the 3R Concept in Makassar City, Indonesia - Nurul Akramila; Fatmawati A. Mappasere; Abdul Mahsyar (Journal of Governance and Public Policy)
Ineffective waste management can lead to the accumulation of waste, which results in environmental damage and low economic income for the community. The purpose of this study was to analyse the participation of the community in the implementation of the 3R circular economy in Makassar City. Qualitative research methods were used in this study. The data sources of this research were collected through interviews, observations, and study of relevant documents. Secondary data was collected by searching data from the Google Scholar database using the Publish or Perish application and Vos Viewer to map the topic. The results and discussion also used the NVivo 12 Plus "Concept Map" analysis tool. The results showed that household participation in 3R-based waste management towards a circular economy in Makassar City cannot be said to be achieved. This is because the main principle of the circular economy is waste management with the 3R principle, but the overall conclusion is that the 3R principle in waste management does not occur properly in the Ujung Pandang sub-district of Makassar City. The novelty of this research lies in its integration of qualitative methodologies, advanced data analysis tools like NVivo 12 Plus, and a focus on mapping the community's participation within a 3R circular economy framework in a specific urban context. This study uniquely identifies gaps in the practical implementation of 3R principles, providing new insights into the socio-environmental and economic dynamics of waste management. This research contributes to the government and the community so that they can collaborate more in managing waste optimally. Good waste management will have a significant impact on health, a clean environment, and economic value.